Perancangan Aplikasi Terjemahan Ayat Suci Al-Qur’an Menggunakan Algoritma Winnowing - Yuda Yuda (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Al-Qur’an is the holy book of Muslims which has different parts of the translation between different verses. This makes it more difficult for ordinary people who do not understand Arabic to know the content and meaning of the holy Qur'an. Technological developments can assist in facilitating the search for information, especially the translation of the holy verses of the Qur'an. The string matching technique is one way to facilitate searching and the winnowing algorithm is included in one of the string matching algorithms. The winnowing algorithm is one of the algorithms with the fingerprinting document method. The fingerprinting document will generate a hash value which is called a fingerprint. This fingerprinting will be the basis for comparing the selected documents. In finding the value of the winnowing algorithm translation application using the jaccard similarity calculation. Search conducted using the winnowing algorithm to search based on the name of the surah found in the holy Qur'an. And the output is in the form of a verse found in the letter along with its translation. Search using the winnowing algorithm has a 100% similarity level between text and pattern searches